TRAINING ON PRODUCING LOW-CALORIE TOFU-BASED SOUVENIRS IN KAMPUNG EMAS SEYEGAN, SUPPORTED BY UNY - Dewi Eka Murniati; Martono; Yosep Efendi; Wika Rinawati; Nur Aulia Wijayanti; Fitroh Anugrah Kusuma Yudha; Luthfi Fahmi Roshaanatun; Aji Abdussalim (PT. Jurnal Center Indonesia Publisher, 2025)
The Community Service Program (PKM) in Kampung Emas Seyegan was implemented to address local economic stagnation caused by limited product innovation, weak business management, and low digital marketing literacy among the Krapyak tofu industry center. Through a participatory approach and an applied training model, this program focuses on improving production and marketing capacities by developing healthy culinary products made from low-calorie tofu. The training included the processing of two flagship products—Tofu Rolade and Tofu Dimsum—with the application of food safety standards, flavor diversification, and packaging innovation. In addition, participants received assistance in business management, cost of goods sold (COGS) calculations, branding, as well as digital marketing using social media and e-commerce platforms. The results show a significant increase in production skills, understanding of the value chain, and the ability to downstream local souvenir products. The program successfully fostered an innovative entrepreneurial orientation, strengthened local culinary identity, and has the potential to increase household income and the economic sustainability of the community.